THE IMPLEMENTATION OF STUDENT FACILITATOR AND EXPLAINING LEARNING MODELS TO IMPROVE STUDENT LEARNING OUTCOMES IN IPA SUBJECTS AT SDN BIRO - Azizah Azizah; Rahman Rahman; Gita Khairunnisa (Education Journal, 2020)
Based on field studies, this study aims to improve student learning outcomes through the use of Student Facilitator and Explaining learning models in science subjects class V at SDN Biro. The subjects in this study were students of class V B of SDN Biro with a total of 22 students consisting of 8 male students and 14 female students. This type of research is classroom action research, which is carried out in two cycles, each cycle consisting of several stages: planning, implementing, observing, and reflecting. Classroom action research is said to be successful if it meets the limitation indicator of classical learning outcomes of at least 75 percent. The data obtained from this study include student learning outcomes taken through the provision of tests in the form of multiple choice of 10 numbers. The results of the first cycle showed that the average student learning outcomes were 68.18% with 69.31% of student activity while the percentage of teacher activity in the first cycle was 78% and had fulfilled the sufficient criteria. In the second cycle research the classical completeness average reached a percentage of 85%, and the percentage of teacher activity was 95.45% while the percentage of student activity was 88.63%. Based on the results of the second cycle it can be that learning with the Student Facillitator and Explaining models can improve the learning outcomes of fifth grade students of SDN Biro 2019/2020 school year.